Analisis Faktor Yang Mempengaruhi Perilaku Perencanaan Investasi: Peran Kontrol Diri Sebagai Variabel Moderasi - Rahma Dani Sapitri; Yessi Nesneri (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
Investment planning behavior essentially involves the act of allocating a certain amount of funds in the present with the expectation of gaining profits in the future. This study aims to examine the influence of financial knowledge, financial experience, financial attitudes, and financial skills on investment planning behavior, with self-control as a moderating variable, among students of the Faculty of Economics and Social Sciences at UIN Suska Riau. The study sample consists of 265 respondents, and the data was analyzed using SEM-PLS 4.0. The results indicate that financial attitudes, financial skills, and self-control have a positive and significant influence on investment planning behavior. In contrast, financial knowledge and financial experience do not have a positive and significant effect on investment planning behavior. Furthermore, self-control cannot moderate the influence of financial knowledge, financial experience, financial attitudes, and financial skills on investment planning behavior. The influence of financial knowledge, financial experience, financial attitudes, and financial skills on investment planning behavior among students of the Faculty of Economics and Social Sciences at UIN Suska Riau is 63.6%, with the remaining 36.7% influenced by additional variables not studied.